Is quality of life related to illness and acceptance of illness? - Janusz Kocjan (Kazimierz Wielki University, 2015)
Kocjan Janusz. Is quality of life related to illness and acceptance of illness? Journal of Education, Health and Sport. 2015;5(7):34-42. ISSN 2391-8306. DOI 10.5281/zenodo.19080 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A26-33 https://pbn.nauka.gov.pl/works/574356 http://dx.doi.org/10.5281/zenodo.19080 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 24.06.2015.   IS QUALITY OF LIFE RELATED TO ILLNESS AND ACCEPTANCE OF ILLNESS?   JANUSZ KOCJAN   Medical University of Silesia, Faculty of Medicine, Katowice, Poland   SUMMARY Introduction: Although, that the general well-being is extensively studied in wide range of contexts, still little place is devoting to relationship between acceptance of illness (AIS) and quality of life (QoL), especially among cardiac patients. Aim: The aim of this study was to: (1) determine an association between these two variables; (2) examine relationship between selected variables (age, sex, education level, NYHA class, time since CVDs diagnosis, cardiosurgery intervention and presence of comorbid diseases) and quality of life. Material and methods: The study included 172 patients with diagnose cardiac disease. All participants were examined used standardized questionnaires: Short Form of health survey (SF-36 questionnaire) and Acceptance of Illness Scale (AIS). Results: The patients presented moderate level of illness acceptance and quality of life level. Over than half of participants did not accept their illness. Significant, positive relatioship between AIS and QoL were noted. NYHA class, number of cardiac hospitalization and time since cardiovascular disease diagnosis was negatively correlated with QoL. Conclusions: Findings presented in this study demonstrated, that AIS is strongly related with QoL.    Key words: illness acceptance, quality of life, AIS, QoL, cardiac diseases.